Development and Testing of a Polycentric Knee Joint for Powered Walking Assist Exoskeletons - Séguin, Émélie (Université d'Ottawa / University of Ottawa, 2021)
Loss of mobility and independence directly affects the quality of life of many vulnerable individuals. To address this, researchers have developed wearable walking assist exoskeletons to aid users with their daily activities. While this technology has advanced tremendously in the past decade, current exoskeletons cause discomfort and injuries to the user, leading to device rejection. This research intends to develop a kinematically compatible knee joint suitable for exoskeletons. The proposed knee design can be adapted to accommodate an offset and optimize force delivery. This is achieved by ensuring that the mechanical and biological joint rotation axes are aligned and that the moment arm varies throughout flexion. Model simulations and mechanical testing of fabricated prototypes were achieved to analyze and validate the design. The results confirm the kinematic compatibility of the design and that the moment arm could be varied throughout flexion to achieve optimal and effective moment transfer.
Keywords: Exoskeleton; Knee; Polycentric; Walking Assist Exoskeleton